ANALISA USAHA BUDIDAYA IKAN PATIN (Pangasius pangasius) dan LELE DUMBO (Clarias gariepinus) HASIL SUBTITUSI PELET DENGAN USUS AYAM Di KOLONG BEKAS PENAMBANGAN TIMAH - ENDANG BIDAYANI (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2007)
Patin (Pangasius pangasius) and Dumbo catfish (Clarias gariepinus) is being semi intensively cultured on floating net; in the lakes of tin mining activity called Kolong; by farmers in Bacang village, subdistrict of Bukit Intan, Pangkalpinang regency. This spesies is best suited for culture in kolong because of their well adapted of environmental change; even in a size-limited ponds; for growing normally. Kolong should be the decades in one age. Feeding Patin (Pangasius pangasius) and Dumbo catfish (Clarias gariepinus) cultured with this method should more profitable if we substitute the formulated meals (pellets) with chicken guts, as the alternative feed. The main differences would be on their variabel cost, profit value, Break Event Point (BEP), Return of Invesment (ROI) and Benefit Cost Ratio (B/C)